Resisting Independence : Popular Loyalism in the Revolutionary British Atlantic - Jones, Brad A. (Book collections on Project MUSE., 2021)
"A study of British Loyalism in four British Atlantic port cities - Halifax [Nova Scotia], Kingston [Jamaica], Glasgow, and New York City - during the period of the American Revolution and War for Independence (1765-1783)"--